Trust Me Not: How Ostracism and Job Tension Drive Employees to Hide What They Know - Syifa , Halizah Azzahroh Nur; Sulistiawan, Jovi; Lin, Pie-Kuan (Universitas Airlangga, 2025)
Objective: This study aims to investigate the indirect relationship between interpersonal distrust and knowledge hiding behaviors through two mediating mechanisms, namely workplace ostracism and job tension. By combining social identity, social exchange, and conservation of resources theory, this study addresses the debate on how interpersonal relationships influence defensive knowledge behaviors in high-pressure organizational settings. Design/Methods/Approach: Data were collected through an online survey from 302 employees working in the FMCG manufacturing sector in Indonesia between January and April 2025. The study employed structural equation modeling–Partial Least Squares (SEM-PLS) and Importance–Performance Matrix Analysis (IPMA) to test the hypothesized relationships. Findings: The findings reveal that interpersonal distrust significantly predicts workplace ostracism, which in turn leads to increased job tension. Both workplace ostracism and job tension mediate the effects of distrust on three dimensions of knowledge hiding: playing dumb, evasive hiding, and rationalized hiding. IPMA further highlights workplace ostracism as a critical target for managerial intervention. Originality/Value: This study contributes to the literature by uncovering the psychological and relational pathways through which interpersonal distrust translates into knowledge hiding. It emphasizes the importance of fostering trust and inclusion in the workplace. Practical/Policy implication: IPMA results indicate that workplace ostracism has high importance but relatively low performance in influencing knowledge hiding, suggesting it should be prioritized in managerial interventions. Organizations should build trust-based cultures and reduce exclusionary behaviors to promote knowledge sharing.